Analisis Kinerja Investasi Reksadana Saham Menggunakan Metode Sharpe, Treynor, dan Jensen (Studi Kasus Pada Reksadana Saham Yang Terdaftar di Otoritas Jasa Keuangan Tahun 2023) - Sidik, Yuliani Fajar; Yulia, Iis Anisa; Pranamulia, Agus (Jurnal EMT KITA, 2025)
This study investigates the performance of equity mutual funds in Indonesia using three performance evaluation techniques, namely the Sharpe Index, Treynor Index, and Jensen's Alpha Index. Equity mutual funds are chosen because, in the world of investment instruments, they have the potential for maximum returns for investors. However, this instrument is also associated with quite high risks, so an accurate performance evaluation is needed to guide investors in making better investment choices. The data set in this study is the daily net asset value (NAV) of several selected equity mutual funds for a certain period. IHSG (Composite Stock Price Index) as a benchmark for market performance. The Sharpe Index is used to measure returns on total risk, the Treynor Index measures return on systematic risk and the Jensen Alpha Index is used to examine whether fund managers can generate additional returns compared to the market. The study was conducted on equity mutual funds that were identified as performing well. However, there are also mutual funds whose returns lag the market benchmark. These findings provide investors with an understanding of the relative performance of equity mutual funds and the need to have selection criteria when choosing these funds